Enzymatic Synthesis of the Unnatural Nucleotide 2'‐Deoxyisoguanosine 5'‐Monophosphate. (22nd September 2022) - Zhao, Fuping; Wei, Yifeng; Wang, Xinyu; Zhou, Yan; Tong, Yang; Ang, Ee Lui; Liu, Shengnan; Zhao, Huimin; Zhang, Yan
Abstract: Naturally occurring DNA contains four canonical bases, forming two Watson‐Crick base pairs (adenine‐thymine, guanine‐cytosine). Efforts over the past decades have led to the development of several unnatural base pairs, enabling the synthesis of unnatural DNA with an expanded genetic alphabet. The engineering of organisms capable of de novo biosynthesis of unnatural DNA would have significant technological and philosophical implications, but remains a challenge. Here we report the enzymatic conversion of 2'‐deoxyxanthosine 5'‐monophosphate (dXMP) into deoxyisoguanosine monophosphate (dBMP), a precursor of the unnatural isoguanine‐isocytosine base pair. The reaction is catalyzed by the bacteriophage enzyme PurZ and bacterial PurB, and is a key addition to the toolbox for de novo biosynthesis of unnatural DNA. Abstract : The enzymatic conversion of 2'‐deoxyxanthosine 5'‐monophosphate (dXMP) into deoxyisoguanosine monophosphate (dBMP), a precursor of the unnatural isoguanine‐isocytosine base pair is reported. The reaction is catalyzed by the bacteriophage enzyme PurZ and bacterial PurB, and is a key addition to the toolbox for de novo biosynthesis of unnatural DNA.